Role of Positive Affective Experiences of Transformational Leaderships Impact and Incentives for Creative Performance and Organizational Citizenship Behaviors - Maroofi, Fakhraddin (International Journal of Asian Social Science, 2016)
This research employed an interactionist approach to demonstrate the way that trait PA affects TL and, as a result, affect OCB and creative behavior. The methodological approach of this research is a Quantitative survey of 212 employees and their direct managers from the west of education of Iran in Marivan city. Finding show that the results support the hypothesized moderation effect. A transformational leader who possesses high trait PA may have a stronger relationship with a follower with high trait PA. Therefore, the positive influence of transformational leadership on creative performance was significantly reduced for followers who were higher on the trait PA (ΔR2 =. 03, p<. 05). The same pattern, in which followers’ trait PA appeared to substitute for the influence of transformational leadership, generalized to the outcome of follower OCB as well (ΔR2 =. 05, p<. 01). In this paper discussed theoretical and practical implications of these findings.